Flexible, twistable and plied electrode of stainless steel Cables@Nickel–Cobalt oxide with high electrochemical performance for wearable electronic textiles. (10th July 2020) - Zhang, Tianyun; Wang, Zhennan; Zhu, Aiping; Ran, Fen
Abstract: Effective 1D-shaped current collectors and high capacitance active materials are the key components to meet the demand of high performance of flexible 1D electrode for wearable electronic textiles. In this work, a flexible 1D electrode of stainless steel cables@nickel-cobalt oxide is fabricated for wearable electronic textiles. Surface modified stainless steel cables are developed as 1D-shaped current collector to support binary-metal nickel-cobalt oxides as active materials. Stainless steel cables@nickel-cobalt oxide electrodes with various sizes are prepared by spinning technology, including twisting and plying technologies, owing to the advantages of flexibility, spinnability, and weavability of stainless steel cables. Furthermore, the relationship between the ply numbers of twisted stainless steel cables and the electrochemical performance is discussed; and SSC electrodes with various sizes is measured using different metrics, including non-textile and textile standard yarn numbering systems. The as-obtained electrode shows a high specific capacitance under an operating voltage window of 1.0 V, as length capacitance with 113 × 10 −3 mAh cm −1 at 0.3 mA cm −1, areal capacitance with 449 × 10 −3 mAh cm −2 at 1.2 mA cm −2, volume capacitance 69 mAh cm −3 at 1.0 A cm −3 and linear density capacitance with 433 × 10 −3 mAh N −1 and 0.22 × 10 −3 mAh Tex −1 at 0.6 mA. This work provides a textile perspective on the field of evaluating the performance of the 1D-shaped electrode for energy collection, conversion, and storage applications. Graphical abstract: Image 1 Highligts: A facile method for surface modification of stainless steel cables is developed. Various flexible 1D electrodes are prepared by twisting and plying technologies. The electrode shows a high capacity of 406 mF cm −1 at 0.3 mA cm −1 . The electrochemical performance is measured through Nt (Tex) and Nm (N).